2023
DOI: 10.1001/amajethics.2023.545
|View full text |Cite
|
Sign up to set email alerts
|

How Body Mass Index Compromises Care of Patients With Disabilities

Abstract: The history of body mass index (BMI) is intertwined with the development of anthropometric statistics used to classify and measure human variation, an intellectual foundation of eugenics. While useful in analyzing population trends in relative body weight, BMI possesses multiple shortcomings when used as an individualized health screening tool. These limitations compromise the just care of people with disabilities, especially patients with achondroplasia and Down syndrome, for whose care BMI use contributes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A longitudinal cohort study in Malawi showed that children with disabilities also have significantly higher mortality rates from severe acute malnutrition than children without disabilities (mortality HR 2.29, 95% CI 1.51 to 3.45). 5 Further, while some types of impairments may make the use of standardised measures of nutritional status invalid (eg, growth restriction or limb difference), 6 these conditions do not occur at sufficiently high prevalence to distort estimates drawn from large samples. Indeed, previous descriptive analysis of the Multiple Indicator Cluster Survey (MICS) has shown that children with functional difficulty in the walking, playing and fine motor domains have the highest prevalence of stunting, wasting and underweight.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal cohort study in Malawi showed that children with disabilities also have significantly higher mortality rates from severe acute malnutrition than children without disabilities (mortality HR 2.29, 95% CI 1.51 to 3.45). 5 Further, while some types of impairments may make the use of standardised measures of nutritional status invalid (eg, growth restriction or limb difference), 6 these conditions do not occur at sufficiently high prevalence to distort estimates drawn from large samples. Indeed, previous descriptive analysis of the Multiple Indicator Cluster Survey (MICS) has shown that children with functional difficulty in the walking, playing and fine motor domains have the highest prevalence of stunting, wasting and underweight.…”
Section: Introductionmentioning
confidence: 99%